Kinetics of torquetenovirus DNA load in a recent kidney transplant recipient with mild SARS‐CoV‐2 infection and a failed antibody response. Issue 2 (6th December 2020) - Querido, Sara; Calça, Rita; Weigert, André; Francisco, Diogo; Adragão, Teresa; Ana Pessanha, Maria; Gomes, Perpétua; Rodrigues, Luís; Figueira, João M.; Cardoso, Conceição; Machado, Domingos
Abstract: Kidney transplant (KT) recipients are at an increased risk for severe COVID‐19 because of their immunosuppressed state. A 42‐year‐old KT patient was diagnosed with COVID‐19 three months after KT. Despite lymphopenia and several risk factors, he had a mild disease course. Nasopharyngeal real‐time reverse transcriptase polymerase chain reaction for SARS‐CoV‐2 became negative 48 days after detection. SARS‑CoV‑2 IgG antibodies became negative after day 40. TTV DNA load increased with the onset COVID‐19 and reduced after its resolution. This is the first report where TTV DNA load was measured during the course of COVID‐19.